Caracterización clínica y sociodemográfica de población clasificada como desplazada y registrada en el Sisbén en un hospital psiquiátrico en Cali, Colombia (2008-2020) - Montes Martínez, Mateo (2025)
Forced displacement, the crime with the largest number of victims of the Colombian armed conflict, has few analyses emphasizing mental health. This article presents a characterization of this phenomenon, delving into issues of poverty, vulnerability, and types of mental health care for victims. Two methodological approaches are used: a quantitative one, complementing data from a psychiatric care center with information from Sisbén, a database with socioeconomic information used to classify the population according to their living conditions, and a qualitative one, examining patients’ clinical records. Thus, the text describes how the displaced population faces multiple vulnerabilities that combine victimization, poverty, and mental health affectations. This research confirms the high prevalence of depressive and anxiety disorders as reported in the literature. It was found that, despite identifying the condition of forced displacement, this factor has a minimal influence on care, revealing standardized practices. The vulnerability of this group, in terms of poverty, hinders the continuity of care and perpetuates stigmatization, hindering the breaking of the poverty cycle. Therefore, the text highlights the need to address indeterminacy and standardization in caring for special needs populations.